2018
DOI: 10.5604/01.3001.0011.6503
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between a theory of mind and executive functions in preschool children

Abstract: Acquisition of the theory of mind (TOM) is a very important milestone in the development of preschool children. TOM is especially important for the development of children’s social skills. The goal of the present study was to examine the effects of age, gender and executive functions (EF) on the acquisition of TOM. The sample in this study consisted of 116 preschool children aged 36-72 months (mean age 58.8 months, SD= 9.5 months). In relation to the child’s gender, there were 56 girls (48.3%) and 60 boys (51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
(35 reference statements)
0
3
0
1
Order By: Relevance
“…Finally, FB performance has been associated with other aspects of EFs, such as SH (ages 3-8 years) (Blair & Razza, 2007;Gordon et al, 2014;Guajardo et al, 2009;Kara & Selcuk, 2021;Oh & Lewis, 2008) and planning (PL) (Putko & Zlotogorska, 2014). Furthermore, children's scores (ages 8-11 years) in SH (Cassetta et al, 2018) and PL (ages 3-6 years) (Cole & Mitchell, 2000;Longobardi et al, 2021;Memisevic et al, 2018) have also been found to predict FB performance.…”
Section: Relationship Between Fb and Efsmentioning
confidence: 94%
“…Finally, FB performance has been associated with other aspects of EFs, such as SH (ages 3-8 years) (Blair & Razza, 2007;Gordon et al, 2014;Guajardo et al, 2009;Kara & Selcuk, 2021;Oh & Lewis, 2008) and planning (PL) (Putko & Zlotogorska, 2014). Furthermore, children's scores (ages 8-11 years) in SH (Cassetta et al, 2018) and PL (ages 3-6 years) (Cole & Mitchell, 2000;Longobardi et al, 2021;Memisevic et al, 2018) have also been found to predict FB performance.…”
Section: Relationship Between Fb and Efsmentioning
confidence: 94%
“…Adicionalmente, las relaciones diferenciales entre las tareas de FE y TdM son consistentes con investigaciones anteriores, las cuales señalan que las tareas de FE conflictivas como Oso/ Dragón, que implican tanto la inhibición como la MT, suelen relacionarse más fuertemente con la TdM que las tareas de Retraso o la MT sola (Carlson y Moses, 2001;Carlson et al, 2002;Devine & Hughes, 2014;Hala et al, 2003;Hughes y Ensor, 2007;Memisevic et al, 2018). Estudios adicionales con niños son consistentes al evidenciar que el desempeño en tareas de creencias falsas y otras tareas de TdM se puede predecir a partir de tareas que aprovechan las habilidades del funcionamiento ejecutivo como la inhibición de la respuesta, la resolución de conflictos cognitivos y la memoria de trabajo (Carlson et al, 1998;Brock et al, 2018;García-Molina & Clemente-Estevan, 2019;Hughes, 1998;Pesch et al, 2020;Perner & Lang, 2000).…”
Section: Fuente: Elaboración Propiaunclassified
“…Being exposed to several languages helps children understand others better due to learning different ways of using language to relate to others. Since ToM plays a crucial role in social communication and executive functioning, early ToM capabilities can lead to later adaptive behaviors as well as academic success among autistic children ( Memisevic et al, 2018 ; Roselló et al, 2022 ). However, in recent years, the understanding of ToM in autism literature has significantly changed.…”
Section: Introductionmentioning
confidence: 99%